2004
DOI: 10.1029/2003jb002395
|View full text |Cite
|
Sign up to set email alerts
|

One‐dimensional fluid diffusion induced by constant‐rate flow injection: Theoretical analysis and application to the determination of fluid permeability and specific storage of a cored rock sample

Abstract: [1] We describe the conceptual design and first application of a new method for simultaneously measuring the fluid permeability and specific storage of a rock sample. In our laboratory tests, a constant flow rate single-stroke piston pump injects fluid into a cored rock specimen placed between two reservoirs in which fluid pressure is recorded. For this geometry we have derived a new analytic solution of the governing diffusion equation describing the one-dimensional fluid flow. This new analytic solution in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…Confining pressure, shear stresses as well as other factors such as temperature will influence permeability of granite samples (Morrow et al 1986;Song et al 2004;Alam et al 2015). As a result, water infiltration varies at different in situ conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Confining pressure, shear stresses as well as other factors such as temperature will influence permeability of granite samples (Morrow et al 1986;Song et al 2004;Alam et al 2015). As a result, water infiltration varies at different in situ conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This could result in dilation of granite specimen and permeability increase from an early stage of injection. Song et al (2004) found that the permeability of Westerly granite increases with decreasing effective pressure hence increasing pore pressure. The pores in the two sandstones are much less compressible and show negligible deformation at the early pressure stage.…”
Section: Analysis Of Pressurization Rate Changementioning
confidence: 98%
“…Later, Esaki et al [5] enhances the accuracy and efficiency of the mathematical model by considering the effect of storage capacity of the pump system. Song et al [17] introduced more straightforward mathematical model of the technique with less tedious numerical simulation to solve the model.…”
Section: Introductionmentioning
confidence: 99%
“…A sudden change in geologic pore pressure can result in catastrophic hazards (TALWANI and ACREE 1984;REID 1994;IVERSON et al 2000;PAROTIDIS et al 2003;SHAPIRO et al 2003). Pore pressure prediction is essential for modeling various geologic processes, evaluating seismic sensitivity and landslide triggering, the safe design of deep drilling, the production of fluid resources, and the storage of hazardous wastes in geologic formations (SONG et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Flooding of a cylindrical rock sample in a triaxial system is the most commonly used technique to obtain the hydraulic parameters k x and S s in the xdirection (BRACE et al 1968;TRIMMER et al 1980;TRIMMER 1981TRIMMER , 1982OLSEN et al 1985;SONG et al 2004;RENNER 2006, 2007). If j x is constant, and assuming one-dimensional laminar flow through a homogeneous medium in the x-direction, then Eq.…”
Section: Introductionmentioning
confidence: 99%